Play [bi-directional arrows] learn: Susan B. Anthony Middle School site as a neighborhood park design - Hao, Shuang (Kansas State University, 2012)
Neighborhood parks can provide a place for children and teens to satisfy their curiosity and learn about nature. Without an open-space policy or regulation from the city, no park was proposed during the development of the neighborhood adjacent to Susan B. Anthony Middle School in Manhattan, Kansas. People have to cross Highway 113 (Sethchild Road) or Kimball Avenue to the closest parks: Marlatt and Cico. However, neither of them is within walking distance for children and teens in this neighborhood. As a result, families have to build private playgrounds in their own backyards. In addition, technological development makes children and teens prefer staying inside playing video games. Neither private playgrounds nor video games provide interaction with nature or social interaction around nature. This project considers how the middle school site, which sits on approximately 40 acres, can be designed as a neighborhood park to allow children and teens to have close nature access and experiential learning opportunities. To better understand what users really need, interviews with teachers and questionnaires for students determined their current and preferred future use of the school site. In addition, neighborhood children, who are not in the middle school, were interviewed about their play preferences. Observations of the school site usage during school time and after were recorded for design purposes. Six precedents were examined to compare and understand what works to connect children and young teens to nature. After analyzing user needs and physical conditions of the site, a neighborhood park design for the site of Susan B. Anthony Middle School was proposed. The proposed design meets both students’ experiential learning needs and the need of neighborhood children and young teens to connect to nature. Because the 40-acre schoolyard is a nationally recommended size for middle schools, this joint-use schoolyard and park concept can be applied cross the country where needed.
Play and learn
Keywords: Landscape of Learning; Neighborhood Park; Children and Nature; School Design; Experiential Learning; Susan B. Anthony Middle School; Landscape Architecture (0390)